2003
DOI: 10.1128/mcb.23.4.1403-1417.2003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dissection of Mitotic Recombination in the Yeast Saccharomyces cerevisiae

Abstract: Recombination plays a central role in the repair of broken chromosomes in all eukaryotes. We carried out a systematic study of mitotic recombination. Using several assays, we established the chronological sequence of events necessary to repair a single double-strand break. Once a chromosome is broken, yeast cells become immediately committed to recombinational repair. Recombination is completed within an hour and exhibits two kinetic gaps. By using this kinetic framework we also characterized the role played b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
123
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(130 citation statements)
references
References 65 publications
6
123
1
Order By: Relevance
“…Similarly, break processing and strand‐invasion operate during DSB repair by homologous recombination, but on two DNA ends. Not surprisingly, Srs2 is also required for DSB repair involving both ends (Vaze et al , 2002; Aylon et al , 2003) as re‐synthesis of both processed DNA ends would be required to complete the repair.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, break processing and strand‐invasion operate during DSB repair by homologous recombination, but on two DNA ends. Not surprisingly, Srs2 is also required for DSB repair involving both ends (Vaze et al , 2002; Aylon et al , 2003) as re‐synthesis of both processed DNA ends would be required to complete the repair.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, reports from Haber and co-workers (20) and Kupiec and co-workers (19) showed that Srs2 is also needed for the repair of a site-specific double-strand break by synthesis-dependent single-strand annealing or double-ended synthesis-dependent single-strand annealing, the major pathway of gene conversion in mitotic yeast cells. In one of these published studies, the srs2 K41A allele was found to be defective in synthesis-dependent single-strand annealing (20).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the recombination-related phenotypes, the srs2⌬ mutant is partially deficient in the activation of the intra-S DNA damage checkpoint in response to treatment with methylmethane sulfonate (MMS) (18). Additionally, two independent studies (19,20) have implicated SRS2 in DNA double-strand break repair by the synthesis-dependent single-strand annealing mechanism as well. Srs2 also appears to influence the efficiency of single-strand annealing (17).…”
mentioning
confidence: 99%
“…Interestingly, both yeast Srs2 and mammalian RECQ5 have been implicated in antirecombination (see above) and anticrossover pathways (Aylon et al 2003;Ira et al 2003;Paliwal et al 2014). Although the mechanisms involved still need to be established, it is possible that removal of Rad51 from ssDNA is involved in both.…”
Section: Reversibility Of Extended D-loops: a Step In Sdsa And A Mechmentioning
confidence: 99%